“Patok Lele” Traditional Game as a Medium for Building Islamic Character of Students at the Pantai Dalam Guidance Studio, Kuala Lumpur, Malaysia - Fuadi, Ahmad; Sufawi, Muhamamad; Saleh, Muhammad; Sakdiah, Khairaini; Ronaldo, Muhammad; Dzikri, Chalik (International Journal of Islamic Thought and Humanities, 2025)
This research explores the potential of the traditional game Patok Lele as a medium for building Islamic character in children at the Pantai Dalam Guidance Center in Kuala Lumpur. This game not only acts as a physical and recreational activity but also instills Islamic values such as honesty, cooperation, patience, and responsibility. The method employed in this research is a descriptive qualitative approach with data collection through observation, interviews, and documentation. Data was gathered from direct observation of the game's implementation, interviews with participants and program managers, and documentation of activities. The results indicated that the Patok Lele game effectively internalized Islamic values among children. In addition to enhancing social skills, the game strengthens Islamic character by teaching the values of honesty, cooperation, and discipline through authentic experiences. Through this activity, children not only play but also learn in a fun and educational atmosphere, aligning with the principles of Islamic education that emphasize the balance between cognitive, affective, and psychomotor development.